2003
DOI: 10.1007/s00442-003-1286-4
|View full text |Cite
|
Sign up to set email alerts
|

Ecological constraints on extra-pair paternity in the bluethroat

Abstract: The mating system of the bluethroat (Luscinia s. svecica) involves a high level of sperm competition, and consequently a high frequency of extra-pair paternity (EPP). There is considerable variation in the frequency of EPP. Over the course of ten study years in a population in Norway, the frequency has fluctuated between 7% and 33% of young, and 8% and 76% of broods. In this paper, we address the issue of whether ecological factors can explain some of the variation in EPP between years and broods. Factors incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 23 publications
1
60
1
Order By: Relevance
“…Eggs in a clutch are usually laid at 24-h intervals. Breeding is quite synchronous (Johnsen and Lifjeld 2003) with most females starting to lay their eggs during the first 2 weeks of June. Incubation takes about 13 days and the nestlings leave the nest 10-13 days after hatching (Anthonisen et al 1997).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eggs in a clutch are usually laid at 24-h intervals. Breeding is quite synchronous (Johnsen and Lifjeld 2003) with most females starting to lay their eggs during the first 2 weeks of June. Incubation takes about 13 days and the nestlings leave the nest 10-13 days after hatching (Anthonisen et al 1997).…”
Section: Methodsmentioning
confidence: 99%
“…A sexual dimorphism in egg size has previously been reported for a few species (see Cordero et al 2000), but we have no a priori expectation of such a dimorphism in bluethroats. Extra-pair paternity occurs at a frequency of around 30% of young and 50% of clutches in this population (Johnsen and Lifjeld 2003). It is a theoretical possibility that females may differentially allocate resources to eggs in a clutch sired by extra-pair males, as these eggs may represent a relatively higher reproductive value (Johnsen et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Saino et al 1997;Conrad et al 1998;Strohbach et al 1998), while the vast majority of studies report no association between the synchrony of breeding activities and extra-pair reproductive success (e.g. Chuang-Dobbs et al 2001b;Johnsen and Lifjeld 2003;Arlt et al 2004;Kraaijeveld et al 2004;Westneat and Mays 2005;Stewart et al 2006). How the behavioural strategies adopted by each sex towards male conspecifics influence these links between extra-pair mating rates and local synchrony remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Third, adverse conditions may make activities other than attempted usurpation of females a priority for males, their mates, or potential cuckolders. For example, in the bluethroat (Luscinia s. svecica), for those broods that had multiple paternity, mornings with relatively low temperatures were associated with a lower frequency of extra-pair paternity (Johnsen and Lifjeld 2003). Johnsen and Lifjeld (2003) suggested that this lower frequency was because individuals, who might otherwise be engaged in extra-pair copulations, needed to concentrate on foraging during such conditions.…”
mentioning
confidence: 99%